1990
DOI: 10.3109/10715769009109680
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Free Radicals and Nitric Oxide Derivative of Hemoglobin in Rats During Shock Syndrome

Abstract: Free radicals have been postulated to play an important role as mediators in the pathogenesis of shock syndrome and multiple-organ failure. We attempted to directly detect the increased formation of radicals by Electron Spin Resonance (ESR) in animal models of shock, namely the endotoxin (ETX) shock or the hemorrhagic shock of the rat. In freeze-clamped lung tissue, a small but significant increase of a free radical signal was detected after ETX application. In the blood of rats under ETX shock, a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
44
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(53 citation statements)
references
References 17 publications
8
44
1
Order By: Relevance
“…Previous studies have already shown that LPS and NO donor treatment increase the HbNO concentration in blood, and clear HbNO spectra have been successfully obtained using the EPR method without any modifications (10,28,31,67,69). However, we and others failed to detect the distinct EPR signal of HbNO in the blood of normal humans or animals.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Previous studies have already shown that LPS and NO donor treatment increase the HbNO concentration in blood, and clear HbNO spectra have been successfully obtained using the EPR method without any modifications (10,28,31,67,69). However, we and others failed to detect the distinct EPR signal of HbNO in the blood of normal humans or animals.…”
Section: Discussioncontrasting
confidence: 45%
“…Hb is known to bind to NO, resulting in the formation of HbNO, which has a characteristic EPR spectrum, and hence is used as a spin-trapping agent for NO in lipopolysaccharide (LPS)-treated (67,69) and NO donor-administered (10,28) animals.…”
mentioning
confidence: 99%
“…This observation questions either the contribution of peroxynitrite to tissue damage or the relationship between peroxynitrite and nitrotyrosine. The fact that recent evidence suggests that ortho-nitrotyrosine may be formed from a number of sources that do not necessarily involve peroxynitrite, e.g., the reaction between nitrite and hypochlorous acid (10,32), may go in some way to explain our findings.…”
Section: Discussionmentioning
confidence: 59%
“…17 Endotoxin administration source of serum NO 0 2 /NO 0 3 . 45 in the lung; in other words, NO measured in the exhaled air 10. Sieber CC, Lopez-Talavera JC, Groszmann RJ.…”
mentioning
confidence: 99%